BJSS rewards five top students - The Star (2012)
NATIONAL junior cricket player Derek Michael Doraisingam and footballer Mohammad Faris Mohamad Yusof were among five recipients of the Principal Award at the Bukit Jalil Sports School (BJSS) Pre-University certificate presentation ceremony in Kuala Lumpur recently